Larengeal chondrosarcoma (case report) (Eurasian Medical Research Periodical, 2026)
Chondrosarcoma of the larynx is a rare type of laryngeal tumor that is often underestimated by patients and diagnosed at late stages of the disease. Clinical, histological, and radiological correlation is necessary for the diagnosis of chondrosarcoma of the larynx. Although the prognosis is relatively favorable, conservative surgical excision with negative margins is recommended. This article describes a case of chondrosarcoma of the larynx in a patient who required total laryngectomy.